Immunomodulatory function and anti-tumor mechanism of natural polysaccharides: A review - Ying, Yang; Hao, Wu (Frontiers in Immunology, 2023)
Polysaccharides extracted from natural resources have attracted extensive attention in biomedical research and pharmaceutical fields, due to their medical values in anti-tumor, immunomodulation, drug delivery, and many other aspects. At present, a variety of natural polysaccharides have been developed as adjuvant drugs in clinical application. Benefit from their structural variability, polysaccharides have great potential in regulating cellular signals. Some polysaccharides exert direct anti-tumor effects by inducing cell cycle arrest and apoptosis, while majority polysaccharides can regulate the host immune system and indirectly inhibit tumor through activating non-specific immune response or specific immune response. As the role of microenvironment in the process of tumor development has been gradually revealed, some polysaccharides were found to inhibit the proliferation and metastasis of tumor cells via tumoral niche modulation. Here, we focused on natural polysaccharides with biomedical application potential, reviewed the recent advancement in their immunomodulation function and highlighting the importance of their signaling transduction feature for the antitumor drug development.